TELAAH KRITIS PUTUSAN SIDANG ITSBAT PENETAPAN AWAL BULAN QAMARIYAH DI INDONESIA DALAM PERSPEKTIF USHUL FIKIH - Qulub, Siti Tatmainul (Al-Ahkam, 2015)
This study aims to criticize the implementation of the Itsbat Conference (a conference determining the beginning of Qamariyah month) implemented by the government through the Ministry of Religious Affairs. Among the important issues is what is the main factor causing the disagreements and how is the position of Itsbat Conference in usul fiqh point of view? Research carried out on the results of Itsbat Conference on Ramadhan and Syawwal in 1381 H - 1434 H / 1962 AD - 2011 AD. The study concluded that the disagreements tend to occur due to the critical height of the new moon and approach in determining the new moon. According to usul fiqh, Itsbat Conference can be seen in multiple perspectives; The first, it is an obligation on the government as a representation of imam, to facilitate and support the implementation of the totality of praying; Second, it is a form of state responsibility to the people to promote unity, especially in the implementation of praying, by minimizing disagreements and conflicts. Thirdly, to realize maslaá¸¥at â€˜Ämmah, the essence of the maqÄá¹£id al-sharÄ«â€™ah. Itsbat Conference is one example of maslaá¸¥at á¸¥Äjiyyah needed to complete the fasting of Ramadhan, â€˜Idul Fitr, and Idul Adha